(untitled) (Publicacions de la Universitat de València, 2024)
This book contributes to the field of pragmatic variation in World Englishes by analysing the pragmatic markers ‘kind of’ and ‘sort of’. After a general review of their history and current use, the book offers a contrastive study of their frequency, semantics and pragmatic values in four varieties of English, as represented in the GloWbE corpus. These are, on the one hand, the two most influential inner circle varieties of English, those spoken in the United States and Great Britain, and, on the other, two outer circle varieties spoken in former colonies of these two countries, namely the Philippines and Singapore respectively. The results strengthen the understanding of the effects of global processes such as Americanization and glocalization on pragmatic variation and illustrate phenomena of linguistic convergence and divergence across space. Este libro contribuye al campo de la variación pragmática en las lenguas inglesas del mundo analizando los marcadores pragmáticos “kind of” y “sort of”. Tras una revisión general de su historia y su uso actual, se ofrece un estudio contrastivo de su frecuencia, semántica y valores pragmáticos en cuatro variedades de inglés, representadas en el corpus GloWbE. Se trata, por un lado, de las dos variedades más influyentes del inglés del círculo interno, las habladas en Estados Unidos y Gran Bretaña, y, por otro, de dos variedades del círculo externo habladas en antiguas colonias de estos dos países, Filipinas y Singapur, respectivamente. Los resultados refuerzan la comprensión de los efectos de procesos globales como la americanización y la glocalización en la variación pragmática e ilustran fenómenos de convergencia y divergencia lingüística a través del espacio.